DEVELOPMENT OF VACCINES BASED ON ADENOVIRAL VECTORS: A REVIEW OF FOREIGN CLINICAL STUDIES (PART 2) - L. V. Cherenova (SPb RAACI, 2017)
Currently, many human infectious diseases do not developed effective methods of treatment and prevention. One of the latest successes of biotechnology is the use of adenoviral vectors carrying immunodominant antigens  of various pathogens as genetically engineered vaccines  both  preventive and therapeutic. The use of genetic  engineering technologies allows not  to use in the  manufacture of vaccines  live viruses and  bacteria, reduces  the  time  needed for vaccine  creation and  production of new vaccines.  Adenoviral vectors  naturally penetrate into human cells, causing a rather  long and significant  both humoral and cellular immune response. In the second  part of review, we provide  information about  the ongoing  worldwide  clinical  trials of adenoviral vector-based vaccines against various infectious diseases such as influenza, malaria, Ebola haemorrhagic fever, tuberculosis, hepatitis and  several others, like as to consider selection parameters of volunteers, vaccination schedule, doses of drug administration, results of completed experiments, and preliminary data  on currently ongoing  research.